FAMILY COUNSELING SEBAGAI UPAYA MEWUJUDKAN KETAHANAN KELUARGA BAGI MUSLIMAT NU TRENGGALEK - Mutrofin; Muhammad Dwi Toriyono; Shinta Alimatul Islam; Muhammad Sholihuddin Zuhdi (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2024)
Understanding the principles of counseling in forming a maslahah family should be based on the principle of benefit for both the individual and society. Therefore, counselors must understand these principles in providing support and guidance to families. Conflicts that occur in families often become problems that are so complex that they require the right approach to resolve them. So, it is important to understand and apply various techniques and strategies for resolving conflicts in the family. This research aims to describe explicitly the understanding of the principles of counseling in realizing family resilience for the Muslimat NU community. Apart from that, it also explains the approaches and strategies used in counseling in an effort to create family resilience. The method used in qualitative with a case study type in the Muslimat NU Trenggalek community. The result of the research show that it is time for the Muslimat NU community to upgrade their understanding of family counseling. They must be pro-active in trying to create a family that is physically and mentally healthy, peaceful, so that it can bring about a prosperous family that is able to overcome various problems in everyday life. So, the Muslimat NU community, which is generally filled with mothers, does not experience psychological stress because of the many demands. Of course, with extensive knowledge and always up to date with the latest information. The hope is that all problems can be resolved well based on the right approach and strategy  Keywords: Family Counseling, Family Recilience, Muslimat NU Community